Grounding And Solutions of Ecological Sustainability, Stomatology, And Human Health Problems in Scientific-Practical-Experiments - Amrulloyevich , Gafforov Sunnatullo; Rahimovna , Mo’minova Dilnoza; Qahramonovich, Nazarov Ulug’bek; Samandarovna, Madaminova Nodira; Axmadovich , Sobirov Alijon; Sunnatulloyevna , Gafforova Sevara (Journal of Ecohumanism, 2024)
The results of a long-term scientific study on the negative impact of chemical, physical, biological, physical factors on the organism of workers and environmental environment of industrial enterprises of the Republic of Uzbekistan and neighboring state regions on the cause of the workplaces, the ecogigienic state in the ecological control regime and the production process were comprehensively evaluated. The authors say that to eliminate the influence of negative factors of the ecogigienic system on the human body, it is necessary not only to conduct activities in the area of one state or one territory but also to simultaneously fight the existing states, non-governmental societies and people in the land sphere, to promote environmental concepts in the education widely.